1983
DOI: 10.1016/0035-9203(83)90130-x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sialoglycoproteins and Plasmodium falciparum invasion

Abstract: Human erythrocytes with a deficiency in glycophorin A (En(a-) cells) and glycophorin B (S-s-U- and S-s-U+ cells) show significant resistance in vitro to invasion by Plasmodium falciparum merozoites. Treatment of normal erythrocytes with trypsin and chymotrypsin also reduced invasion. Trypsinization of S-s- and En(a-) red cells, a process which removes the T1 peptide of glycophorins A and C, produced cells almost refractory to invasion. The human K562 erythroleukaemia cell line, which also expresses glycophorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Cleavage of sialic acid from erythrocytes with neuraminidase treatment greatly reduces erythrocyte invasion by some parasite lines, but produces only modest reduction by others (1,2,6,(8)(9)(10). Erythrocytes genetically deficient in glycophorin molecules, which contain the majority of erythrocyte sialic acid (1 1), have confirmed this diversity in the invasion characteristics of P. falciparum (1,5,9,12).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cleavage of sialic acid from erythrocytes with neuraminidase treatment greatly reduces erythrocyte invasion by some parasite lines, but produces only modest reduction by others (1,2,6,(8)(9)(10). Erythrocytes genetically deficient in glycophorin molecules, which contain the majority of erythrocyte sialic acid (1 1), have confirmed this diversity in the invasion characteristics of P. falciparum (1,5,9,12).…”
Section: Introductionmentioning
confidence: 89%
“…Recently several studies have focused on erythrocyte sialic acid and its role in invasion of erythrocytes by the human malaria parasite Plasmodium falciparum (1)(2)(3)(4)(5)(6)(7). Some studies have shown that different lines of P. falciparum vary in their dependence on erythrocyte sialic acid for effective invasion of red blood cells (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the fre quency of S-s-(Su) as observed in this series of Hausa population is relatively high. In vitro studies [2,3,12,13] have shown that S-s-red cells are relatively re sistant to invasion by P. falciparum: we did not attempt to correlate the presence of malaria with that of the red cell antigens in these donors, but it would be of interest to conduct such an epidemiological study on non-immune children living where ma laria is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to erythrocyte invasion by Plasmodium vivax, which is dependent on the interaction between the parasite Duffy binding protein (DBP) (5) and the erythrocyte Duffy antigen (14), P. falciparum is able to use multiple alternative receptor-ligand interactions to achieve successful invasion (7,12,19,28,30). Investigations of the erythrocyte receptors utilized by the merozoite for invasion have been carried out with erythrocytes deficient in particular surface molecules (8,12,25), antibodies that bind to these molecules (13), or enzymes that modify protein and carbohydrate domains on these molecules (4,7,8,19,26). The principal enzymes used have been neuraminidase (which cleaves sialic acid groups from surface glycoproteins and glycolipids) and trypsin (which cleaves the peptide backbone of a number of surface proteins).…”
mentioning
confidence: 99%